The effectiveness of health education via audio-visual demonstrations of HIV-AIDS - Emi Sutrisminah; Yuli Astuti; Aina Nurus Sofa (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
In Indonesia, the case of HIV-AIDS is still an epidemic that hinders the realization of the Sustainable Development Goals (SDGs), especially in the third indicator. The highest incidence in the age group of 25-49 years (70.4%). The reason for this high case is that health education is still low so the information obtained is not optimal. The purpose of this study was to determine the effectiveness of health education through audio-visual demonstration media about HIV-AIDS. This research was conducted in the Kaliwungu Public Health Center working area with a total sample of 73 people. This research includes quantitative pre-experiment with One Group PreTest and PostTest Design. The sampling technique used was purposive sampling. The instrument used is a knowledge and attitude questionnaire. Data analysis using the Mc Nemar test. The results of the univariate analysis stated that there was a difference in knowledge before and after the intervention, namely from sufficient (49.3%) to good (60.3%). In attitude, there is also a difference in values before and after the intervention, which was initially only positive (84.9%) to (95.9%). Bivariate analysis showed that there were significant differences in the knowledge and attitudes of women of childbearing age before and after being given health education with a value of (0.000) and (0.008). This shows that health education through AVISDEM media can increase knowledge and attitudes about HIV-AIDS. It is hoped that health service providers will intensify health education for women of childbearing age in an effort to prevent HIV-AIDS. Abstrak: Di Indonesia kasus HIV-AIDS masih menjadi epidemi yang menghambat terwujudnya Sustainable Development Goals (SDG’s) khususnya pada indikator ketiga. Angka kejadian tertinggi berada di usia 25-49 tahun(70,4%). Penyebab tingginya kasus ini karena pendidikan kesehatan yang masih rendah sehingga informasi yang diperoleh belum optimal. Tujuan penelitian ini adalah untuk mengetahui efektifitas pendidikan kesehatan melalui media audio-visual demonstrasi tentang HIV-AIDS. Penelitian ini dilaksanakan di Wilayah Kerja Puskesmas Kaliwungu dengan jumlah sampel sebanyak 73 orang. Penelitian ini termasuk kuantitatif pra-eksperimen dengan One Group Pre-Test and Post-Test Design. Teknik pengambilan sampel menggunakan purposive sampling. Instrumen yang digunakan adalah kuesioner pengetahuan dan sikap. Analisis data menggunakan Uji Mc Nemar. Hasil analisis univariat menyatakan ada perbedaan pengetahuan sebelum dan sesudah intervensi yaitu dari cukup (49,3%) menjadi baik (60,3%). Pada sikap juga terdapat perbedaan nilai sebelum dan sesudah intervensi yang awalnya bersikap positif hanya (84,9%) menjadi (95,9%). Analisis Bivariat menunjukkan adanya perbedaan yang signifikan terhadap pengetahuan dan sikap wanita usia subur sebelum dan sesudah diberikan pendidikan kesehatan dengan nilai (0,000) dan (0,008). Hal ini menunjukkan bahwa pendidikan kesehatan melalui media AVISDEM mampu meningkatkan pengetahuan dan sikap tentang HIV-AIDS. Diharapkan pemberi pelayanan kesehatan lebih menggencarkan penyuluhan kesehatan kepada Wanita Usia Subur sebagai upaya pencegahan HIV-AIDS.